Les partis politiques et les élections européennes un an après : bilan et perspectives - Seiler, Daniel; Duquette, Michel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1980)
This study covers the one-year period since the first election of the European Assembly by universal suffrage, the results of which were rather misleading. The authors attempt to elaborate a conceptual framework capable of analyzing empirically the programs and ideological stands of the parties in the Strasbourg Chamber as they have evolved since the election. As a point of reference, the analysis has recourse to three socio-political cleavages which were observable throughout late European history or tend to appear in the modem context of political life; these include the divisions between 1) "bourgeois" and working class parties; 2) europeanist versus nationalist parties, and 3) industralist (or productivist) as opposed to "ecological" party formations. A detailed examination of both the interventions of euro-deputies in Assembly debates, and data recorded in several interviews with some deputies during this first year of their mandate, reflects not only the existing constellations of power and party alliances within the Assembly that reaffirm themselves on specific issues, but also the potential coalitions which may arise due to the rapidly changing political scene. These new coalitions, which tend to form more easily among members of different parties who share common interests with regard to social and economic issues, may eventually serve to overcome the traditional ideological divisions among parties. In terms of the near future, it doesn't matter so much whether the Euro-right or the Euro-left will succeed in imposing its majority in the Assembly, but whether the European Parliament itself, as an institution, will be able to demonstrate that it can have an effective and more representative voice in the formulation of EEC policies.